Shadow Education and Its Academic Effects in Bangladesh: A Vygotskian Perspective - Alam, Md. Bayezid; Zhu, Zhiyong (Frontiers in Psychology, 2022)
Private tutoring is a newly emerging field of research, which remains largely under-theorized. Adopting the Vygotskian philosophy of learning as an analytical lens, this qualitative study conceptualized the academic effects of private tutoring in Bangladeshi higher secondary educational context. The primary data were gathered from 18 semi-structured interviews with tutored students, parents, and teachers. The data from secondary sources were also collected to supplement the primary data. A thematic procedure was used to analyze the data. The analysis demonstrated two important findings. First, students internalized knowledge and skills through scaffolding by their private tutors, which eliminated their learning deficiencies and boosted their academic credentials. Second, private tutoring induced long-term deficiencies as it provided rote learning. It dulled students’ critical thinking and made them dependent on others. The paper carried significant theoretical implications by producing a unique insight into students’ learning in the shadows from a Vygotskian perspective.